Respuesta :
Answer:
f(-2) = 5
Step-by-step explanation:
Put the value where the variable is, and do the arithmetic.
f(-2) = 3(-2)² -7 = 3(4) -7
f(-2) = 5
[tex]\huge\bf\underline{\underline{\pink{A}\orange{N}\blue{S}\green{W}\red{E}\purple{R:-}}}[/tex]
We have to find the value of f(-2) so we must place x = -2 in f(x) equation to get our required answer.
By Solving & simplifying we get,
[tex]:\implies\sf{f(-2) = 3 {x}^{2} - 7}[/tex]
[tex]:\implies\sf{f(-2) = 3 {( - 2)}^{2} - 7}[/tex]
[tex]:\implies\sf{f(-2) = 3 \times 4 - 7}[/tex]
[tex]:\implies\sf{f(-2) = 12 - 7}[/tex]
[tex]:\implies\sf{f(-2) = 5}[/tex]
- The value of f(-2) is 5.